Enolase inhibition alters metabolic hormones and inflammatory factors to promote neuroprotection in spinal cord injury. (October 2020) - Polcyn, Rachel; Capone, Mollie; Matzelle, Denise; Hossain, Azim; Chandran, Raghavendar; Banik, Naren L.; Haque, Azizul
Abstract: Enolase inhibition is a potential therapeutic strategy currently being investigated for treatment of spinal cord injury (SCI) as it reduces pro-inflammatory cytokines and chemokines, alters metabolic factors, and reduces gliosis in acute SCI. Herein, the role of enolase in SCI has been examined to better understand the effects of this enzyme on inflammation, metabolic hormones, glial cell activation, and neuroprotection under these shorter injury conditions. Immunohistochemical analyses of inflammatory markers vimentin, Cox-2, and caspase-1 indicated that enolase inhibition attenuated the elevated levels of inflammation seen following SCI. Iba1, GFAP, NFP, and CSPG staining indicated that enolase inhibition with prolonged administration of ENOblock reduced microglia/astrocyte activation and lead to enhanced neuroprotection in SCI. An analysis of metabolic hormones revealed that ENOblock treatment significantly upregulated plasma concentrations of peptide YY, glucagon-like peptide 1, glucose-dependent insulinotropic peptide, glucagon, and insulin hormones as compared to vehicle-treated controls (Mann-Whitney, p ≤ 0.05). ENOblock did not have a significant effect on plasma concentrations of pancreatic polypeptide. Interestingly, ENOblock treatment inhibited chondroitin sulfate proteoglycan (CSPG), which is produced by activated glia and serves to block regrowth of axons across the lesion site following injury. An increased level of NeuN and MBP with reduced caspase-1 was detected in SCI tissues after ENOblock treatment, suggesting preservation of myelin and induction of neuroprotection. ENOblock also induced improved motor function in SCI rats, indicating a role for enolase in modulating inflammatory and metabolic factors in SCI with important implications for clinical consideration. Highlights: Enolase expression and activity is increased after spinal cord injury (SCI) in rats, promoting inflammation and damage. Elevation of enolase upregulates the production of inflammatory cytokines and chemokines, and metabolic factors in SCI. Enolase inhibition reduces pro-inflammatory cytokines and chemokines, alters metabolic factors in SCI. Enolase inhibitor (ENOblock) attenuates chondroitin sulfate proteoglycan (CSPG) formation, preserving myelination in SCI. Inhibition of enolase activationimproves neuroprotection and motor function in SCI.